Educação sexual: jogo educativo para aprendizagem de alunos com deficiência intelectual - Vieira, Andréia Santiago (2017)
The approach to sexual education issues is a theme imbued with prejudices and taboos. The purpose of this dissertation is to present a contextualization proposal for the teaching of subjects related to Sexual Education in relation to the target audience of Special Education through an educational game. The themes addressed in the educational game called Path of Life are linked to the exercise of citizenship because they propose the discussion about concepts allusive to the phases of human life. The game contains categories / levels that emerged from the center of student interest and were understood as a healthy way of life. In this sense, they integrate into the content of the game questions that contemplate axes, namely: self-care and sexuality. The typology chosen was the Participatory Research of a qualitative nature. The trajectory that involves the initial construction of the work consists of a review of the specialized literature on the subject, and the theoretical basis is based on Sexual Education, Intellectual Disability and Educational Product. Next, the fieldwork is carried out, taking as a locus of the research, a group of the evening hours composed of young people and adults with Intellectual Disability of a School Unit of the City Hall of Duque de Caxias (RJ). To better meet the inherent specificities of people with Intellectual Disability, previous activities are carried out to support the development of the prototype of the game and the accomplishment of the tests of the prototype of the game with the students. The collected data constitute the source of analysis and interpretation, through the use of the Content Analysis Methodology. The analyzes are built from narratives from parents and students surveyed and correlate the line of research social relations and citizenship. As a result, with respect to the expressed content on the 3rd level (sexuality) game, you realize that if it were not the collective construction of educational game, very likely, almost no knowledge about matters relating to sex education was being worked with the students. From this perspective, the themes that anticipate training in sexual education serve as a barometer face the need to think of actions in these terms in a school context. It is also observed that students need to be heard about their anxieties from adolescence and adult life. We see, therefore, that the role of sexual education evidenced in the Life Path game is not merely to inform, but educate, guide, provide spaces for dialogue and reflection that allows the teenager / adult with Intellectual Disabilities build their own ethical identity and aesthetics. Thus, it can contribute to the construction of the teaching and learning process in order to collaborate to build citizenship, improve knowledge and develop skills and competences in the areas of biology and health education in students with Intellectual Disabilities.